Spontaneous Spinal Epidural Abscess Presenting in a Previously Healthy Young Adult Man - Andrew M. McDonald; Jason L. Rollins (Case Reports in Medicine)
We report a case of spontaneous spinal epidural abscess (SEA) with initial chief complaint of shoulder pain and no appreciable neurologic symptoms. Since outcomes of SEA appear to be related to the degree of neurologic deficit at the time of intervention, we explore opportunities for earlier diagnosis.